2022
DOI: 10.3390/life12091446
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Phenolic Profile, Antioxidant, and Anti-Inflammatory Activities of Salvadora oleoides Decene. and Salvadora persica L. Fruits and Aerial Part Extracts

Abstract: (1) Background: The objective of this study was to investigate the potential of Salvadora oleoides (S. oleoides) and Salvadora persica (S. persica) polyphenols as antioxidant and anti-inflammatory agents. (2) Methods: Aerial parts and fruits of S. oleoides and S. persica were collected from the periphery of District Bhakkar, Punjab, Pakistan. Methanol extracts were prepared using the Soxhlet extraction technique. Extract yield varied from 8.15 to 19.6 g/100 g dry plant material. RP-HPLC revealed the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…17 Moreover, S. persica has demonstrated its efficacy as an anti-inflammatory and antioxidant agent through multiple trials, exhibiting therapeutic properties. 26 It modifies the structure of nitric oxide synthase isoforms and reduces the levels of pro-inflammatory cytokines such as IL-1, IL-6, IL-8, TNF, and IFN. 27,28 Additionally, it enhances the anti-inflammatory and antioxidant effects at the site of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, S. persica has demonstrated its efficacy as an anti-inflammatory and antioxidant agent through multiple trials, exhibiting therapeutic properties. 26 It modifies the structure of nitric oxide synthase isoforms and reduces the levels of pro-inflammatory cytokines such as IL-1, IL-6, IL-8, TNF, and IFN. 27,28 Additionally, it enhances the anti-inflammatory and antioxidant effects at the site of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols attract immense attention for their potential nutraceutical and pharmaceutical impacts on human health, due to their inherent biological properties such as antioxidant, anti-allergic, antibacterial, anti-inflammatory, antitumor, anti-diabetic, and antiviral [18][19][20][21][22][23][24][25][26][27][28][29][30]. They also keep blood vessels healthy and flexible by managing Life 2022, 12, 1768 2 of 23 blood pressure levels that is helpful for good blood circulation [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the study by Hussain and colleagues demonstrated that polyphenols extracted from Salvadora oleoides Decene. and Salvadora persica L. fruit and aerial parts could potentially be used as antioxidant, analgesic, and anti-inflammatory agents [9]. Other than having applications as nutraceuticals and therapeutics, plant-derived compounds can also be used as pesticides.…”
mentioning
confidence: 99%